PERANAN PENAGIHAN TUNGGAKAN PAJAK TERHADAP PERTUMBUHAN TUNGGAKAN PAJAK - Ovilya Rambu Ana Awa; Norman Duma Sitinjak (University of Merdeka Malang, 2017)
This study aimed to analyze the effectiveness of the collection of tax arrears on STO Stone and to analyze the contribution of delinquent tax collection to the final balance of tax arrears on STO Stone. Taxes become the backbone of cash income for the country, therefore the government ensures that the tax revenue to meet the target. But it does not always go smoothly. Arrears can occur either because of a lack of awareness of taxpayers and the inability of taxpayer funds to pay their tax debts. To handle this, the government, or in this case the Tax Office Primary spearhead that tax arrears may be getting smaller over time. Target's disbursement of tax arrears that have been determined by the Regional Office with a wide range of considerations. The effectiveness of tax arrears collection that demonstrates the ability of the collection of tax arrears based on the amount of tax revenue over the billing section targeted. The biggest tax arrears from 2012 to 2013, due to the balance of the year 2012 plus a legal product which was published in 2013 reduced payments or reductions in 2013. DOI: https://doi.org/10.26905/ap.v3i1.1328